Recent advances and approaches in the metal-free synthesis of 1, 3-oxazole derivatives. Issue 17 (2nd September 2022) - Shinde, Suraj; Inamdar, Shaukatali; Shinde, Mahadev; Kushwaha, Narvadeshwar; Obakachi, Vincent; Girase, Pankaj; Kushwaha, Babita; Dhawan, Sanjeev; Kumar, Vishal; Karpoormath, Rajshekhar
Abstract: This review presents an overview of recent advances and approaches in the metal-free synthesis of substituted 1, 3-oxazole derivatives, which will enable organic researchers to identify the challenges in synthesizing these five-membered heterocyclic compounds. Specifically, 1, 3-oxazole moiety containing compounds have been reported to possess a wide variety of applications, including in the medicinal, pharmaceutical, agrochemical and material sciences sectors. We classified these nonmetal-catalyzed synthetic approaches on the basis of their starting material's functionality that was used to synthesize 1, 3-oxazole. This review covers the last six-year (2016–2021) of nonmetal catalyzed/mediated synthetic approaches. Graphical Abstract: UF0001